Edukasi Latihan Batuk Efektif pada Penderita TB Paru dengan Masalah Ketidakefektifan Bersihan Jalan Nafas - Sri Legawati; Khairunnisa Batubara; R. Sri Rezeki (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
One of the infectious diseases that is a problem in the world is Pulmonary TB with the main symptoms of shortness of breath, chest pain when coughing and breathing due to airway obstruction. If not treated, it can cause death, so it needs treatment, one of which is with effective coughing exercises. The activity begins with measuring the respiratory rate, then effective coughing exercise therapy. Education is carried out to relieve the respiratory tract by expelling sputum for Pulmonary TB sufferers and in collaboration with local village officials. The method used in this activity is counseling on effective coughing exercises from a team of nursing lecturers and nursing students during Field Learning Practices of 32 respondents. The results obtained from respondents before being given education were 32 people with a high respiratory rate> 25x / minute and after education there was a change in the normal range of 23-25x / minute as many as 26 people and 6 others with a high respiratory rate> 25x / minute. The output of the PkM that has been implemented is expected to increase the respiratory rate after effective coughing exercises are applied in the community.